2015
DOI: 10.1017/s003329171500166x
|View full text |Cite
|
Sign up to set email alerts
|

Altered functioning of reward circuitry in youth offspring of parents with bipolar disorder

Abstract: Background Offspring of parents with BD (BO) are at higher risk of bipolar disorder (BD) than offspring of parents with non-BD psychopathology (NBO), although both groups are at higher risk than offspring of psychiatrically healthy parents (HC) for other affective and psychiatric disorders. Abnormal functioning in reward circuitry has been demonstrated previously in individuals with BD. We aimed to determine whether activation and functional connectivity in this circuitry during risky decision-making different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 70 publications
(155 reference statements)
4
36
1
Order By: Relevance
“…Two recent fMRI studies have also observed functional abnormalities during reward tasks in OBP. In one report, elevated negative bilateral VS-right VLPFC connectivity to win and loss trials (vs. control trials) distinguished OBP from both offspring of healthy parents and offspring of parents with non-BD disorders (Manelis et al, 2016). Another study observed elevated left VLPFC activation and reduced pregenual ACC-VLPFC connectivity during reward processing in healthy OBP relative to healthy control youths (Singh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent fMRI studies have also observed functional abnormalities during reward tasks in OBP. In one report, elevated negative bilateral VS-right VLPFC connectivity to win and loss trials (vs. control trials) distinguished OBP from both offspring of healthy parents and offspring of parents with non-BD disorders (Manelis et al, 2016). Another study observed elevated left VLPFC activation and reduced pregenual ACC-VLPFC connectivity during reward processing in healthy OBP relative to healthy control youths (Singh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies have identified functional abnormalities within neural circuitry supporting information processing domains known to be disturbed in BD, such as reward processing (Phillips and Swartz, 2014). As parental history of BD is one of the most robust risk factors for developing BD (Birmaher et al, 2009), recent neuroimaging studies have focused on examining reward-related neural circuitry in offspring of bipolar parents (OBP), and have yielded valuable insights into neural processes that may predispose to BD (Manelis et al, 2016, Singh et al, 2014). Yet, while OBP are at elevated risk for BD, many do not develop the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…No additional article was found in the manual search. Most of the studies were conducted in adolescents [23][24][25][26][27][28][29][30] with only two studies conducted in young adults [31,32]. The samples of subjects at-risk for BD were comprised of healthy offspring of bipolar patients [25,28,29], healthy and symptomatic offspring of bipolar patients [24,26,27,30], symptomatic offspring of bipolar patients [23] and healthy and symptomatic offspring or siblings of bipolar patients [31,32].…”
Section: Study Selectionmentioning
confidence: 99%
“…The samples of subjects at-risk for BD were comprised of healthy offspring of bipolar patients [25,28,29], healthy and symptomatic offspring of bipolar patients [24,26,27,30], symptomatic offspring of bipolar patients [23] and healthy and symptomatic offspring or siblings of bipolar patients [31,32]. Some studies were conducted by the same research groups, with partially overlapping samples [23,26,27,30] The studies focused in 4 functional imaging domains: 2 studies employed an emotion processing task [23,26]; 2 studies employed a cognitive-affective task [25,31]; 3 studies employed a reward processing task [27,28,30] and 3 were resting state fMRI studies [24,29,32]. Table 1 resume the main methodological characteristics and results of the selected studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation